Minard revisited: exploring augmented reality in information design - Marques, Ana Beatriz (2021)
This study intends to test and confirm the interest and viability of incorporating augmented reality (AR) technologies in cultural mediation driven by information design, focusing on narrative representation. It is specifically intended to explore semantic relations between reality and virtuality in augmented narratives, ie. expanded narratives through the multimodality enhanced by the use of interactive processes based in augmented reality systems. Departing from Charles Minard’s Figurative Map (1869), three experiments were conducted, in order to reinterpret the program embodied in that artefact, testing several hypotheses in which, through augmented reality, the combination of different modes and media configures different semantic relations between real and virtual. The action-reflection approach undertaken with Figurative Map experiments enabled us to observe and openly systematize different augmented reality functions regarding the physical instance, which can potentially expand traditional forms of information design. Although they are not entirely extrapolatable, the proposal of virtual functions regarding reality were repurposed and adapted from the illustration field, specifically from the semantic relation between text and image. It is acknowledged that this is an open model to be reconsidered and reformulated through several action-reflection iterations and fostered through the narrative study.